2010
DOI: 10.1093/carcin/bgq076
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in selenoprotein genes increase risk of colorectal cancer

Abstract: Low selenium (Se) status correlates with increased risk of colorectal cancer (CRC). Since Se exerts its biological roles through the selenoproteins, genetic variations in selenoprotein genes may influence susceptibility to CRC. This study analysed 12 single-nucleotide polymorphisms (SNPs) in selenoprotein genes [glutathione peroxidase 1 (GPX1), GPX4, 15 kDa selenoprotein (SEP15), selenoprotein S (SELS), selenoprotein P (SEPP1) and thioredoxin reductase 2 (TXNRD2)] and in genes that code for a key protein in Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
123
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(130 citation statements)
references
References 40 publications
4
123
1
2
Order By: Relevance
“…Associations between six single-nucleotide polymorphisms (SNPs) of the earlier-mentioned five genes and CRC have been reported in different ethnic groups (Smith et al, 2001;Landi et al, 2003Landi et al, , 2005Krzesniak et al, 2004;Jiang et al, 2005;McGreavey et al, 2005;Murtaugh et al, 2005;Slattery et al, 2005Slattery et al, , 2006Berndt et al, 2006;Huang et al, 2006;Koh et al, 2006;Kuriki et al, 2006;Matsuo et al, 2006;Moreno et al, 2006;Theodoropoulos et al, 2006;Tranah et al, 2006;Hansen et al, 2007;Kang et al, 2007;Stern et al, 2007;Vogel et al, 2007;Yin et al, 2007;Kury et al, 2008;Funke et al, 2009;Khatami et al, 2009;Tsilidis et al, 2009;Yang et al, 2009;Engin et al, 2010;Meplan et al, 2010;Loh et al, 2011;Wu et al, 2011;Crous-Bou et al, 2012;Gil et al, 2012). These six variants comprised rs12917 and rs2308321 of MGMT, rs1229984 of ADH1B, rs4880 of SOD2, rs2228001 of XPC, and rs1801282 of PPARG.…”
Section: Introductionmentioning
confidence: 99%
“…Associations between six single-nucleotide polymorphisms (SNPs) of the earlier-mentioned five genes and CRC have been reported in different ethnic groups (Smith et al, 2001;Landi et al, 2003Landi et al, , 2005Krzesniak et al, 2004;Jiang et al, 2005;McGreavey et al, 2005;Murtaugh et al, 2005;Slattery et al, 2005Slattery et al, , 2006Berndt et al, 2006;Huang et al, 2006;Koh et al, 2006;Kuriki et al, 2006;Matsuo et al, 2006;Moreno et al, 2006;Theodoropoulos et al, 2006;Tranah et al, 2006;Hansen et al, 2007;Kang et al, 2007;Stern et al, 2007;Vogel et al, 2007;Yin et al, 2007;Kury et al, 2008;Funke et al, 2009;Khatami et al, 2009;Tsilidis et al, 2009;Yang et al, 2009;Engin et al, 2010;Meplan et al, 2010;Loh et al, 2011;Wu et al, 2011;Crous-Bou et al, 2012;Gil et al, 2012). These six variants comprised rs12917 and rs2308321 of MGMT, rs1229984 of ADH1B, rs4880 of SOD2, rs2228001 of XPC, and rs1801282 of PPARG.…”
Section: Introductionmentioning
confidence: 99%
“…3 Variations in selenoprotein genes have been found to be associated with increased cancer risk. 4,5 Transgenic mice with reduced selenoprotein expression manifest precancerous changes. 6,7 Human studies have shown reduced cancer risk and DNA damage after selenium supplementation among those with lower basal plasma selenium.…”
Section: Introductionmentioning
confidence: 99%
“…In the murine intestine, GPx4 mRNA is one of the most abundant selenoprotein transcripts (8); genetic variant analysis of the human GPX4 gene links it to malignant disease risk in the gastrointestinal tract (9,11). Investigation of intestinal GPx4 has so far been limited to the mRNA level (33,36) and to the measurement of GPx4 activity in mouse tissue homogenates (44).…”
Section: Discussionmentioning
confidence: 99%
“…A constant level of GPx4 mRNA during periods of limited selenium availability as against the concomitant degradation of other GPx isoforms such as GPx1 reflects the high ranking of GPx4 in the so-called selenoprotein hierarchy (32) and argues for an important role of this protein in enterocytes. Intriguingly, a function of GPx4 as a candidate mediator of selenium-dependent chemoprevention in the colon arises from studies on the association of a single nucleotide polymorphism (rs713041) in the human GPX4 gene with colorectal adenoma and colorectal cancer risk (9,11,18). The enzymatic capacity of GPx4 extends beyond those of other hydroperoxide-degrading GPx isoforms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation